(untitled) (Semiárida, 2020)
The aim of this work 15 to identify the calanoid copepods of different water bodies of the province of la Pampa. 78 samples were taken from permanent and non-permanent environments. Boeckella gracilis, B. poopoensis and Notodiaptomus incompositus were identified. A diagnosis o, the species and hydrology, pH, salinity, Secchi transparency of the ponds are given.